2005
DOI: 10.1111/j.1349-7006.2005.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia‐inducible factor‐1α in esophageal squamous cell carcinoma

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a transcription factor that plays an important role in tumor growth and metastasis by regulating energy metabolism and inducing angiogenesis. Elevated levels of HIF-1α α α α, a subunit of HIF-1, are noted in various malignant tumors, but it is unclear whether this is so in esophageal carcinoma. The purpose of this study was to evaluate the implications of HIF-1α α α α expression in esophageal squamous cell carcinoma. In 215 patients with esophageal carcinoma, we examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…To evaluate the statistically significant difference in the ratio of cancerous EPAS1 mRNA level to histopathologically unchanged tissue EPAS1 mRNA level between the three DNA methylation ranges (0%-1% methylation, 1%-10% methylation, and 10%-100% methylation), the nonparametric Kruskal-Wallis test was used. HIF1A mRNA levels were increased in cancerous compared with noncancerous tissue (8,11,12,33,34). However, other studies reported a constant HIF1A mRNA level in tumor cells and suggested mainly posttranslational regulation of HIF1A expression (35)(36)(37), which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 83%
“…To evaluate the statistically significant difference in the ratio of cancerous EPAS1 mRNA level to histopathologically unchanged tissue EPAS1 mRNA level between the three DNA methylation ranges (0%-1% methylation, 1%-10% methylation, and 10%-100% methylation), the nonparametric Kruskal-Wallis test was used. HIF1A mRNA levels were increased in cancerous compared with noncancerous tissue (8,11,12,33,34). However, other studies reported a constant HIF1A mRNA level in tumor cells and suggested mainly posttranslational regulation of HIF1A expression (35)(36)(37), which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 83%
“…As a fast-growing cancer, ESCC has a hypoxic microenvironment and metabolic disturbance. Hypoxia suppresses the apoptosis of cancer cells, resulting in the resistance to chemotherapeutic agents and even treatment failure (Matsuyama et al, 2005;Tzao et al, 2008). As shown in our results (Figure 4), HIF-1a siRNA alone or in combination with cisplatin strongly induced apoptosis of ESCC TE-1 cell, which resulted in the growth suppression of transplanted ESCC in nude mice.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, targeting HIF-1a may serve as a viable anticancer strategy to be used in clinics (Kurokawa et al, 2003;Kimura et al, 2004;Matsuyama et al, 2005). Herein, using the strategy of silencing HIF1a with targeted siRNA, we identified that HIF-1a siRNA could effectively inhibit the growth of transplanted ESCC in nude mice, down-regulate the HIF-1α mRNA and protein expression, and induce ESCC TE-1 cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations